Empowerment of Farmer Group in The Processing of Cow Animal Waste into Liquid Organic Fertilizer in Paddy Field (Talenta Publisher, 2022)
Lowland rice is the main commodity crop for the Dos Tahi farmer group in Nagori Bandar Rakyat, Bandar District, Simalungun Regency. However, the scarcity of fertilizers is an inhibiting factor in the process of cultivating rice plants. Many people have livestock and one of them is cattle. However, people still find it difficult to process cow dung. Cow dung waste can be processed into liquid organic fertilizer from both liquid waste and solid waste. The training on making liquid organic fertilizer from cow dung was a suggestion from the community. It is hoped that liquid organic fertilizer can be a solution for the community to anticipate the difficulty of access to fertilizer in lowland rice cultivation.